Weight Change and its Related Factors Among Women after Breast Cancer Diagnosis in Selected Hospitals in Peninsular Malaysia - Yong, Heng Yaw (2011)
The purpose of this cross-sectional study was to determine the prevalence and magnitude of weight change before and after breast cancer diagnosis and to examine the differences in dietary intake, physical activity and psychological factors among the weight change groups. A total of 368 women diagnosed with breast cancer were recruited from eight hospitals and four breast cancer support groups in Peninsular Malaysia. Majority of women in this study were Malay (57.1%), aged > 40 years (92.1%), married (82.6%), unemployed (69.3%) and had completed secondary education (51.9%). Most women were diagnosed with breast cancer at stage I (31.8%) and stage II (41.0%), and had undergone surgery (mastectomy, 79.6%), chemotherapy (82.9%) and radiotherapy (79.6%). The mean weight change and percentage of weight change from a year preceding breast cancer diagnosis to study entry were 2.73 ± 8.05 kg and 5.17 ± 14.06%, respectively. More women (63.3%) reported weight gain rather than weight loss (36.7%) with higher percentage reporting ≥ 5% weight gain (47.8%) than ≥ 5% weight loss (22%). The study showed that respondents had decreased their intakes of high fat foods (18.8–65.5%), added fat food (28.3–48.9%), low fat food (10.6–18.8%), red meat, pork and poultry (20.1–51.1%) and high sugar foods (42.1–60.9%) but increased their intake of fish (42.7%), fruits and vegetables (62.8%) and whole grain (28.5%). Dairy products were avoided (46.8–80.7%) by these women. For physical activity, about 41.6% did not make any adjustments to their physical activity after breast cancer diagnosis. The mean total daily energy of women was 1350 ± 411kcal. Less than half (48.4%) had energy from carbohydrate, protein (37.0%) and fat (45.9%) within the recommended ranges, respectively. Most of the women consumed < 8 servings of grains and cereal products (87.2%), < 3 servings of vegetables (97.8%), < 2 servings of fruits (80.7%) and <1 serving of milk and dairy products (84.0%). Two-thirds of women (59.9%) had ≥ 2servings of meat/fish/poultry/legumes. Nearly all women (92.4%) did not currently consume alcohol. Most women (80.4%) had moderate and high physical activity level while 19.6% reported low intensity physical activity. Nearly all women were currently not depressed (91%) or stressed (94%) and about 80% of were currently not anxious. The selfesteem of the women was considered moderate, with a mean total score of 20.23 ± 3.40. Age at diagnosis, change in fish and whole grain intakes were associated with weight changes after breast cancer diagnosis. Older women (> 51 years) gained less weight (0.91 ± 6.80kg) compared to younger women with women between 20-40 age group gained the greatest amount of weight (4.68 ± 7.03kg). Women who stopped fish intake had the greatest weight loss (-4.04 ± 5.12kg) while those who decreased fish intake after breast cancer diagnosis had the least weight gain (0.69 ± 5.74kg). Women who increased (0.68 ± 7.38kg) whole grains consumption gained less weight compared to those who stopped (4.16 ± 11.60kg) or decreased (3.85 ± 7.27kg) whole grains consumption. The adjusted mean number of servings from fruits and vegetables and dairy products differed significantly among the weight change groups. Compared to other weight change groups, women in > 10% weight gain group had the lowest fruit and vegetable servings (1.58 ± 0.12 servings/day) and highest servings of dairy products (0.41 ± 0.05 servings/day). However, no significant difference was observed in other dietary intake, physical activity and psychosocial well-being variables among the weight change groups. In conclusion, weight gain after breast cancer diagnosis was evident in this sample of women. This study showed that dietary factors but not physical activity or psychological factor were significantly associated with weight change. Future studies are needed to examine the association between physical activity and psychological factors with weight change among breast cancer survivors. Nevertheless, for breast cancer survivors, attainment of healthy body weight through dietary modification and physical activity is essential to reduce the risk of cancer recurrence as well as chronic diseases